Facile synthesis of three‐dimensional NiCo2O4@Co3O4 nanowire array for application in supercapacitors. (1st June 2018) - Yao, Shushan; Zhi, Lifei; Guo, Jin; Yan, Shijian; Zhang, Mingang
Abstract : A three‐dimensional NiCo2 O4 @Co3 O4 hybrid array on Ni foam electrode for supercapacitors was synthesised via a facile two‐step hydrothermal method, in which the NiCo2 O4 was self‐assembled on the Co3 O4 nanowire grown on Ni foam. Moreover, the electrochemical properties of the binder‐free electrodes were studied by cyclic voltammograms, galvanostatic charge/discharge tests and electrochemical impedance spectroscopy. Electrochemical characterisations indicated that the unique nano‐architecture exhibited excellent electrochemical properties of a high capacitance (1075 F/g), good rate (102.4%), cycling stability (92.6%), which were superior to the pristine Co3 O4 nanowire. The results clearly confirmed that growing NiCo2 O4 on Co3 O4 nanowire could substantially improve the capacitive performance of Co3 O4 materials.